If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(r+3)=2(r-3)=53
We move all terms to the left:
5(r+3)-(2(r-3))=0
We multiply parentheses
5r-(2(r-3))+15=0
We calculate terms in parentheses: -(2(r-3)), so:We get rid of parentheses
2(r-3)
We multiply parentheses
2r-6
Back to the equation:
-(2r-6)
5r-2r+6+15=0
We add all the numbers together, and all the variables
3r+21=0
We move all terms containing r to the left, all other terms to the right
3r=-21
r=-21/3
r=-7
| 0.8=22/x | | p/2+86=92 | | 2+3(4x-5)=8 | | (4x=15-3x)2 | | 7x–2=4x-50 | | 8+6d=32 | | y-(-64)=27 | | 7d=–903 | | 18x+-5=-60 | | 5v=350 | | -3(g+71)=-36 | | s÷8=9 | | h7=30 | | -28=h/8-36 | | -7+y=0 | | t–10=–24 | | y+-53=-33 | | 24=3y+y | | 2∙(3x–6)=-4x–22 | | 7x(x+4)=18 | | 2+7k=-75 | | 0.0005/y=0.01 | | –4k=596 | | 4n–2=46 | | 3.x+1=4 | | -y4.6=12 | | m−66=168 | | 14+10h=4 | | 7+y=87 | | 2.2x+6=11 | | 2.7w=-7.02 | | y+29=-18 |